Continuous Improvement in Construction Project Inventory Systems: An XP-Based Investigation during the Warranty Phase - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research explores the importance of effective management in the context of construction projects, with a particular focus on the warranty phase and inventory systems. An efficient inventory system is critical in ensuring the smooth operation of construction projects involving the management of materials, equipment, and other supplies. This research focuses on common challenges in inventory management, including accurate stock monitoring and inventory risk management. This research proposes a Continuous Improvement approach, with the implementation of Extreme Programming (XP), to systematically detect, analyze, and address issues in the inventory system of construction projects on an ongoing basis. The warranty phase in the construction project cycle is identified as a critical period that requires special attention to construction quality and performance. The research stages involved data collection, application development, and user acceptance analysis. The results included identifying project needs through interviews, surveys, and observations and developing an XP-based application to improve inventory management. Feature testing and user acceptance analysis showed that this application can meet the needs of construction projects with a user satisfaction rate of 87 percent. This research is expected to make a real contribution toward improving the efficiency and effectiveness of construction projects through responsive and adaptive inventory solutions.